Differentiation of Human Induced Pluripotent Stem Cells to Mammary-like Organoids - Ying Qu; Bingchen Han; Bowen Gao; Shikha Bose; Yiping Gong; Kolja Wawrowsky; Armando E. Giuliano; Dhruv Sareen; Xiaojiang Cui (Stem Cell Reports, 2017)
Human induced pluripotent stem cells (iPSCs) can give rise to multiple cell types and hold great promise in regenerative medicine and disease-modeling applications. We have developed a reliable two-step protocol to generate human mammary-like organoids from iPSCs. Non-neural ectoderm-cell-containing spheres, referred to as mEBs, were first differentiated and enriched from iPSCs using MammoCult medium. Gene expression profile analysis suggested that mammary gland function-associated signaling pathways were hallmarks of 10-day differentiated mEBs. We then generated mammary-like organoids from 10-day mEBs using 3D floating mixed gel culture and a three-stage differentiation procedure. These organoids expressed common breast tissue, luminal, and basal markers, including estrogen receptor, and could be induced to produce milk protein. These results demonstrate that human iPSCs can be directed in vitro toward mammary lineage differentiation. Our findings provide an iPSC-based model for studying regulation of normal mammary cell fate and function as well as breast disease development.